The Technical Progress and Problems to Be Solved of Thick Coal Seam Mining in China - Jiacheng Wang (International Conference on Ground Control in Mining, 2011)
The current state of thick seam coal mining methods is illustrated in three typical cases of thick seam longwall mining, each pointing out the outstanding achievements in top-coal caving mining and large cutting height mining in China. At the same time, based on current thick seam mining practices in China, some problems urgently need to be solved. These include improving the recovery ratio of coal reserves, determination of overburden strata pressure, shield support selection, supporting methods for large cross-section in-seam roadways, top coal bulk flow theory, and gas flow and control technology. In addition, the rational production capacity should be studied from both economic and technological perspectives in order to optimize coal recovery and efficiency.